Expression of ADAM metalloproteases during transforming growth factor β-induced senescence in breast cancer cells - Alyahya, Linda (Kansas State University, 2017)
Cellular senescence is a state of irreversible cell cycle arrest in response to non-lethal stress. In cancer cells, senescence can be induced by chemotherapy, radiation, or signals from the tumor microenvironment, such as transforming growth factor β (TGFβ). Senescent cells are metabolically active and have altered gene expression compared to their non-senescent counterparts. Senescent cells release a wide variety of factors, including extracellular domains of transmembrane proteins that require proteolytic cleavage by specific proteases. ADAMs (A Disintegrin and Metalloprotease domain-containing proteins) are enzymes that cleave many transmembrane proteins, such as growth factor precursors or adhesion molecules, and thus may act as sheddases in senescent cells. Here, we investigate ADAM expression levels during TGFβ- induced cellular senescence. SUM149PT and SUM102PT breast cancer cells were incubated with TGFβ, followed by treatment with high doses of paclitaxel to remove actively proliferating, non-senescent cells. Induction of cellular senescence was examined by evaluating changes in cell size and granularity, and by β-galactosidase staining. ADAM mRNA levels were measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR). Among several ADAMs tested, ADAM12 mRNA was significantly upregulated in senescent cells. In addition, we demonstrated that ADAM12 knock-down leads to decreased activation of epidermal growth factor receptor (EGFR), an important modulator of cancer cell growth, survival, and metastasis. This effect of ADAM12 knock-down was likely due to a diminished release of soluble EGF or EGF-like ligands from cells. Since senescent cells often release increased amounts of these ligands, ADAM12 may modulate the senescence secretome in senescent breast cancer cells.
Keywords: Senescence; Signaling; Receptor; Protease; SecretionCancer